2022
DOI: 10.3390/vaccines11010095
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Booster Vaccine Hesitancy among Hemodialysis Patients in Saudi Arabia Using the Health Belief Model: A Multi-Centre Experience

Abstract: Objective: Vaccination hesitance for the COVID-19 booster dosage among hemodialysis patients is an important barrier in reducing morbidity and mortality linked to COVID-19 infection. Hence, this study aimed to explore the predictors of the third (booster) dose of COVID-19 vaccine intention among CKD patients on hemodialysis from the Kingdom of Saudi Arabia (KSA). Methods: This study was a multi-center cross-sectional study conducted at four dialysis centers in KSA from 13 February 2022 to 21 June 2022. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…This finding is consistent with both quantitative and qualitative data from studies that have shown that people living with CKD, including patients on dialysis and kidney transplant recipients, are quite concerned or feel vulnerable about contracting COVID-19. 40 - 42 We also found differences in this perceived risk by sex, with the female sex being associated with expressing more concern about contracting COVID-19, which coincides with findings from various populations in the literature. 43 - 46 In addition, those who expressed concern about contracting SARS-CoV-2 were more likely to have sought out information about COVID-19, in the last 12 months.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is consistent with both quantitative and qualitative data from studies that have shown that people living with CKD, including patients on dialysis and kidney transplant recipients, are quite concerned or feel vulnerable about contracting COVID-19. 40 - 42 We also found differences in this perceived risk by sex, with the female sex being associated with expressing more concern about contracting COVID-19, which coincides with findings from various populations in the literature. 43 - 46 In addition, those who expressed concern about contracting SARS-CoV-2 were more likely to have sought out information about COVID-19, in the last 12 months.…”
Section: Discussionsupporting
confidence: 89%
“…Surveys administered among patients undergoing hemodialysis in Saudi Arabia, Italy, and France also found that that many respondents expressed positive perceptions regarding the benefits or effectiveness of the COVID-19 vaccines despite the high level of concern about contracting COVID-19. 42 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between COVID-19 vaccination and lower risks of COVID-19-related hospitalization or death, 6,7 but due to waning vaccine immunity over time, researchers have emphasized the need for additional booster campaigns, particularly for vulnerable populations such as CDR. To date, only Alobaidi et al 9 reported that 22% of hemodialysis patients had reluctance to take up the COVID-19 booster vaccine. Our study indicates that booster campaigns did not achieve the same level of coverage as that observed for the two initial doses, with even worse coverage in the matched-control group.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent systematic review examining the relationships between Health Belief Model constructs and COVID-19 vaccination intention included 109 studies but only 13 articles explored booster vaccines, 8 and only 1 of these 13 articles explored the booster vaccine hesitancy in hemodialysis patients. 8,9 Such findings led us to undertake investigations on vaccination coverage for booster doses. Another challenging consequence of the COVID-19 pandemic for CDR was the reduction in kidney transplant activity.…”
Section: Introductionmentioning
confidence: 99%